P-177 Evaluation of joint working between the renal and palliative care teams in a hospital at east london. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Aiman Entwistle, Ngai Mun; Cove-Smith, Andrea; Clifford, Margaret; Forbes, Suzanne; Go, Jaryn; Phillips, Clare
Abstract : Introduction: Identifying dialysis patients who are deteriorating and require a palliative care approach is challenging. Few have advance care planning (ACP) discussions and the majority die in hospital (Elliott & Gessert, 2016; Davison, 2010). Joint working between the dialysis team and the Specialist Palliative Care team (SPC) was introduced following the recommendations of the UK End of Life Care Strategy (NHS Kidney Care, 2009). Dialysis patients likely to be in the last year of life according to the Gold Standards Framework (GSF) prognostic criteria were added to a 'Cause for Concern' register and discussed at a monthly renal/palliative care Multi-Disciplinary Meeting (MDM) attended by the hospital and community SPC teams. We aim to evaluate the impact of renal/SPC joint working. Methods: Firstly, we reviewed records of all dialysis patients three months before and 15 months after the joint working began. Secondly, we reviewed records of dialysis patients who died over a one-year-period before and after the introduction of the joint working. Statistical tests were performed to compare the situation pre- and post- introduction of the joint working. Thirdly, semi-structured interviews were conducted with renal staff and the data analysed using thematic analysis. Results: The proportion of dialysis patients being offered an ACP discussion increased by five-fold (p=8.4E-04), ACP discussion documentation increased from zero to 3.5% (p=3.7E-03) and proportion with Coordinate My Care (CMC) increased from zero to 3.14% (p=7.4E-03). The staff interviewed (n=8) highlighted the benefits of working alongside the SPC team, especially on symptom management and community support. Conclusion: Introduction of the joint working appears to have improved ACP and delivery of palliative care to dialysis patients. It is hoped that further embedding routine screening with GSF prognostic criteria, MDM discussions and renal-SPC collaboration will continue to improve palliative care for dialysis patients.